Evaluate the phosphorus application response in potatoes under high phosphorus soil test in Florida - Amanpreet Kaur Sandhu; Ayush K. Sharma; Navdeep Kaur; Simranpreet K. Sidhu; Ravinder Singh; Lincoln Zotarelli; Kelly Morgan; Christian Christensen; Lakesh K. Sharma (Farming System)
Phosphorus (P) is an indispensable nutrient for agricultural crops, existing in both organic and inorganic forms within the soil matrix. However, its runoff and leaching could potentially pollute the natural water bodies worldwide through eutrophication. Despite the elevated soil P levels indicated by soil tests, the potato crop necessitates substantial P fertilization due to its relatively superficial root structure and short growth period, particularly when compared to longer-cycle agronomic crops such as corn or cotton. This investigation was designed to assess the response of potato tuber yield and quality to incremental P fertilizer applications during the 2021 and 2022 growing seasons. The research was performed in the 2021 growing season across two different agricultural sites at the Hastings Agricultural Extension Center (HAEC), incorporating eight varying rates of Triple Super Phosphate (TSP) (formulation 0-46-0% N–P2O5–K), specifically 0, 28, 56, 84, 112, 140, 168, and 224 ​kg P2O5 ha−1. In the subsequent 2022 season, the study expanded to include three additional sites at HAEC, testing six different TSP levels at 0, 22, 45, 67, 90, and 112 ​kg P2O5 ha−1. A randomized complete block design (RCBD) with four replications was employed throughout the 2021 and 2022 seasons. The cumulative data from 2021 to 2022 indicated that total and marketable yields across all sites increased in response to increasing P rates (p ​< ​0.05), exhibiting a linear trend in most locations. When aggregating data from all sites, a quadratic yield response pattern emerged. In 2021, P uptake was statistically significant, with mean values fluctuating between 18.69 and 45.09 ​kg ​P ha−1. The P application was correlated with enhanced total P removal from the soil, though the specific gravity of the tubers remained unaffected by any level of P application. The study results suggest applying P improves potato yield even if the soil test P falls in the high range.